The Effect of Noise Exposure on Blood Pressure and Pulse Rate Elevation Among Workers - Adhenan Samudra, Permana; Rachmaniyah, Rachmaniyah; Arida Ipmawati, Putri (Poltekkes Kemenkes Banjarmasin Jurusan Kesehatan Lingkungan Banjarbaru, 2025)
The noise intensity in the workshop area, specifically in the dynotest room at PT. X, records an average of 103 dB(A). This noise originates from assembly, maintenance, and equipment testing activities. The high noise levels and sustained intensity can significantly increase blood pressure and pulse rates in workers who do not use hearing protection devices (HPDs) while working. This study aims to evaluate the impact of noise on the blood pressure and pulse rates of workers in the workshop area, particularly in the dynotest room at PT. X. The research, which employed an observational approach with a cross-sectional study design, was conducted from December to May 2024, involving 40 workers exposed to noise in the dynotest room at PT. X. Data collected included noise measurements, blood pressure, and pulse rates, which were then analyzed using logistic regression tests. The results showed that the average noise level in the dynotest room was 83.5 dBA, while the peak noise level reached 117.8 dBA. Statistical analysis indicated a significant value (p = 0.001) for the relationship between noise exposure and the blood pressure and pulse rates of workers at PT. X, suggesting a significant increase in these parameters due to noise exposure. Recommendations were made for the company to monitor the health of workers to identify potential health issues arising from noise exposure.